Improvement of key molecular events linked to Alzheimer’s disease pathology using postbiotics - Bulacios, Gabriela Agustina (2023)
In the past 50 years, life expectancy has increased by more than 20 years. One consequence of this increase in longevity is the rise of age-related diseases such as dementia. Alzheimer’s disease (AD) is the most common form of dementia, accounting for 60–70% of cases. AD pathogenesis is not restricted to the neuronal compartment but includes strong interactions with other brain cells, particularly microglia triggering the release of inflammatory mediators, which contribute to disease progression and severity. There is growing evidence revealing the diverse clinical benefits of postbiotics in many prevalent conditions, including neurodegenerative diseases. Here, we tested the ability of bacterial conditioned media (BCM) derived from selected lactic acid bacteria (LAB) strains to regulate core mechanisms relevant to AD pathophysiology in the microglia cell line BV-2. Levilactobacillus brevis CRL 2013, chosen for its efficient production of the neurotransmitter GABA, and Lactobacillus delbrueckii subsp. lactis CRL 581, known for its anti-inflammatory properties, were selected alongside Enterococcus mundtii CRL 35, a LAB strain that can significantly modulate cytokine production. BCM from all 3 strains displayed antioxidant capabilities, reducing oxidative stress triggered by beta-amyloid oligomers (oAβ1–42). Additionally, BCM effectively mitigated the expression of inflammatory cytokines, namely, TNF-α, IL-1β, and IL-6 triggered by oAβ1–42. Furthermore, our study identified that BCM from CRL 581 inhibit the activity of acetylcholinesterase (AChE), a crucial enzyme in AD progression, in both human erythrocytes and mouse brain tissues. Notably, the inhibitory effect was mediated by low-molecular-weight components of the BCM. L. delbrueckii subsp. lactis CRL 581 emerged as a favorable candidate for production of postbiotics with potential benefits for AD therapy since it demonstrated potent antioxidant activity, reduction of cytokine expression, and partial AChE inhibition. On the other hand, E. mundtii CRL 35 showed that the antioxidant activity failed to inhibit AChE and caused induction of iNOS expression, rendering it unsuitable as a potential therapeutic for AD. This study unveils the potential benefits of LAB-derived postbiotics for the development of new avenues for therapeutic interventions for AD.